If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-(x+2)+3(x+2)=4-(x-1)
We move all terms to the left:
-(x+2)+3(x+2)-(4-(x-1))=0
We multiply parentheses
-(x+2)+3x-(4-(x-1))+6=0
We get rid of parentheses
-x+3x-(4-(x-1))-2+6=0
We calculate terms in parentheses: -(4-(x-1)), so:We add all the numbers together, and all the variables
4-(x-1)
determiningTheFunctionDomain -(x-1)+4
We get rid of parentheses
-x+1+4
We add all the numbers together, and all the variables
-1x+5
Back to the equation:
-(-1x+5)
2x-(-1x+5)+4=0
We get rid of parentheses
2x+1x-5+4=0
We add all the numbers together, and all the variables
3x-1=0
We move all terms containing x to the left, all other terms to the right
3x=1
x=1/3
x=1/3
| 4x-10=9x-14 | | -2x-53=-6x+56 | | 7(x-2)+2x=3(x-8)+x-5 | | 12x-7=5x+133 | | 4x+7+6x=12+5x-25 | | X(2x-1)^2-x(2x-1)(2x+1)=0 | | 3/2x-5=7/3 | | 2x+3x+8=6x+5 | | -8x=+16 | | 8n-9=15 | | 1/x=3/2+x | | 6n+18=3(3n–2) | | 1/3x²-5/3x+2=0 | | 8x+6=15x-15 | | x+13=-3+1 | | 3x-1=5x+3-1 | | (x+16)+(8x-7)=180 | | (x+16)+(8x+7)=180 | | 4x+24=5x+44 | | -4-3y=8 | | x+16+8x+7=180 | | 3(x-5)=2(3×-1)-19 | | 3(3)-4y=13 | | 5x+6-9x=9 | | 8x-2x6x=52 | | 1.25+0.2=-1.667x+0.75 | | (3a)=² | | 2(x+5)=83 | | 5x+25=7x-23 | | 82-h-29=18 | | (x-12)(2x+25)=0 | | 3p+2p-p=# |